The prevalence of lower eyelid epiblepharon and its association with refractive errors in Chinese preschool children : a cross-sectional study - Zhuo, Deyi (2021)
Background: To assess the prevalence and demographics of lower eyelid epiblepharon in Chinese preschool children and to evaluate its association with refractive errors. Methods: In this population-based, cross-sectional study, a total of 3170 children aged 3 to 6 years from Beijing, China underwent examinations including weight, height, cycloplegic autorefraction and slit-lamp examination of external eyes. The prevalence of lower eyelid epiblepharon in preschool children was evaluated and its association with age, sex, body mass index (BMI), and refractive errors was analyzed using logistic regression analysis. Results: The prevalence of lower eyelid epiblepharon was 26.2%, which decreased with age, with prevalence in 3-, 4-, 5-, and 6-year-olds of 30.6, 28.0, 15.0, and 14.3%, respectively. Boys had a higher risk of having epiblepharon than girls (OR = 1.41; 95%CI, (1.20–1.66)) and no significant correlation was detected between BMI and epiblepharon after adjusting for age and sex (p = 0.062). Epiblepharon was significantly associated with a higher risk of refractive errors, including astigmatism (OR = 3.41; 95% CI, (2.68–4.33)), myopia (OR = 3.55; 95% CI, (1.86–6.76)), and hyperopia (OR = 1.53; 95% CI, (1.18–1.99)). Conclusions: There is a high prevalence of lower eyelid epiblepharon in Chinese preschool children, particularly among boys and younger children. Preschoolers with lower eyelid epiblepharon are subject to a higher risk of developing astigmatism, myopia, and hyperopia, than those without. Increased attention should be paid to this eyelid abnormality in the preschool population.